Feasible path toward 40–100% renewable energy shares for power supply in France by 2050: A prospective analysis. (1st June 2016) - Krakowski, Vincent; Assoumou, Edi; Mazauric, Vincent; Maïzi, Nadia
Highlights: Combination of thermodynamic framework and energy-planning model. Short-term dynamic of power systems in long-term prospective studies. Approach applied to renewable penetration in the French power system. Major role played by dispatchable power plants, imports and demand-response. Renewable energy penetration may jeopardize power system reliability. Abstract: This paper explores the conditions under which renewable energy sources (RES) penetration could jeopardize power system reliability, as well as which flexibility options could help integrate high levels of RES. For this purpose, we used an energy-planning model from the TIMES family, which provides a realistic representation of power systems and plausible options for their long-term development, completed by a thermodynamic description of power systems to assess their reliability. We applied this model to the case of France and built contrasted scenarios, from 0% to 100% renewable energy penetration by 2050. We also tested different assumptions on Variable Renewable Energy (VRE) production, imports, demand flexibility and biomass potential. We show that high renewable energy penetration would need significant investments in new capacities, new flexibility options along with imports and demand-response, and that it is likely to deteriorate power system reliability if no technologies dedicated to this issue are installed.